Canadian pharmacists as immunizers: Addressing questions related to this new scope of practice - Houle, Sherilyn K. D. (Can J Public Health, 2017)
Currently, pharmacists in nine Canadian provinces can apply for authorization to administer drugs and vaccines by injection following the successful completion of a required training program and with evidence of certification in first aid and cardiopulmonary resuscitation. As more provinces and pharmacists embrace this new scope, questions are being raised about their readiness and ability to provide this public health service. This commentary addresses a number of questions commonly raised about pharmacists as immunizers, taking the position that pharmacists are able and willing to play a larger role in vaccination programs.